PENGEMBANGAN MODUL LATIHAN BERJENJANG DALAM PEMBELAJARAN STOIKIOMETRI SISWA KELAS X MADRASAH ALIYAH NEGERI 2 FILIAL PONTIANAK - Putra, Suryadi; Aunurahman, Aunurrahman; Mering, Aloysius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe abstract thing, rote and counting are the fundamental things that become the difficulties in understanding the chemistry materials for the students. Thus it requires learning media in the form of tiered training module to help the students improving their skill in chemistry learning process and the chemistry learning result especially on the stoichiometry subject. This study aimed to produce the design, the final product, the implementation, and the result of tiered training modules in stoichiometric learning at Madrasah Aliyah Negeri 2 Filial Pontianak. This study was a tiered training module development study by using the development stage of Borg and Gall, with the subject of study was the class X students consist of 22 students. The number of students who passed the test was increased in the posstest result taken after the learning process by using tiered training module which was showed that 68,19% students passed the test and only 31,81% students did not pass the test. It means that there were differences in learning outcomes between learning stoichiometriÂ  by using tiered training module and not. Thus a tiered training module in stoichiometric learning could help the students to learn stoichiometric material easily.Key words: pengembangan, modul latihan berjenjang, stoikiometri, Â